STABILITAS DAN MASA SIMPAN SEDIAAN SUSPENSI KERING ERITROMISIN ETILSUKSINAT DENGAN VARIASI BAHAN PENSUSPENSI - Faradiba Faradiba; Amran Ilyas Tandjung; Nur Fadillah (As-Syifaa Jurnal Farmasi, 2011)
An Investigation on how to know the chemist stability and the expired date on dry suspension formulation of erythromycin ethylsuccinate has been done in variation of suspending agents.Evaluation of Chemical stability has been done by inspection a rate of eritromisin degradation with accelerated stability test by stored sample on temperature above room temperature (250C) that is 30, 40, 50 and 600C during 4 days and decided the remain of the erythromicyn concentration each 1 day (24 hours).The Results is rate of erythromycin degradation in stored by normal temperature (250C) for the formula I, II and III to follow that is 0,00043 day-1; 0,00026 day-1 and 0,00064 day-1.  Th stored time for the formula I, II and III to follow that is 0,7; 1,13; and 0,5 years. The result have been shown that formula II (Gum xanthan as a suspending agent) was the most stable dry suspension chemically.Key Words : Stability , Expired Date,  Dry Suspension , Erythromycin Ethylsuccinate , Suspending Agent